# Maths

Under root 4 raised power minus 3 by 4

1. 👍 0
2. 👎 0
3. 👁 56
1. if you mean this
sqrt(4-3/4) then
remember 4 cubed is 64, the fourth root of 64 is 2sqrt2

1. 👍 0
2. 👎 0

## Similar Questions

1. ### Algebra 1

The problem is: a raised to the 2nd power plus 14a raised to the 5th power plus a raised to the 7th minus 16

2. ### math

Here's my question: Determine if each system has one, two, or no solutions. (Show your work - 3 marks each) a)y=2x^2-2x+1 and y=3x-5 b)y=x^2+3x-16 and y=-x^2-8x-18 Here's my work on the question: a) x=(-b plus/minus sign (square

asked by Alex on January 26, 2015
3. ### Mathematics

Find the values of x when, x raised to the power root x = x raised to the power x whole under root.

asked by Bryan on April 18, 2013
4. ### Maths

Find the values of x when, x raised to the power root x = x raised to the power x whole under root.

asked by Bryan on April 19, 2013
5. ### Math

Find the values of x when, x raised to the power root x = x raised to the power x whole under root.

asked by Shrabasti Saha on April 19, 2013
6. ### Math

Find the values of x when, x raised to the power root x = x raised to the power x whole under root.

asked by Watson on April 19, 2013
7. ### math

9^x - 4 X 3^x = 45. Find x In words: 9 raised to the power x minus 4 multiplied by 3 raised to the power x is equal to 45. Find x.

asked by Khalid on June 21, 2011
8. ### Calculus

Find the functions a) f o g, b) g o f, c) f o f, d) g o g, and their domains. f(x)= square root of x, g(x)= cube root of 1-x These are my answers, but I am not sure about them and I only figured out one domain... that is the part

asked by Chelsea on September 19, 2010
9. ### Calc

Find the functions a) f o g, b) g o f, c) f o f, d) g o g, and their domains. f(x)= square root of x, g(x)= cube root of 1-x These are my answers, but I am not sure about them and I only figured out one domain... that is the part

asked by Chelsea on September 20, 2010
10. ### Calculus

Find the specific solution of the differential equation dy/dx = 4y/x^2 with condition y(−4) = e. y equals negative 1 minus 4 divided by x

asked by nan on March 11, 2016

More Similar Questions